Nivel de ansiedad y discapacidad física en un paciente adulto - Torres Torres, Maria Fernanda (2019)
A physical disability due to an amputation is a social and emotional impact for the patient who suffers it and their relatives, reflecting feelings of sadness, frustration, worry, fear, negativity, and low self-esteem, they feel they are discriminated against and therefore to have feelings of inferiority reaching high levels of anxiety. Different techniques were used for data collection and patient history, which were structured in six sessions, including the assessment of the different psychometric tests to establish the level of anxiety and rule out any depressive symptoms and end with a structural diagnosis based on the criteria of the DSM-5 The objective of this research was to develop a therapeutic scheme with a cognitive-behavioral approach where goals and techniques are exposed to reduce the symptomatology of anxiety in the patient. It is necessary to highlight the importance of individual psychological accompaniment in hospital centers contributing to the comprehensive rehabilitation of patients who face this situation and work together with the doctor an psychologist using different therapeutic approaches. Finally, it is recommended that the collaboration of practitioners from the clinical psychology area be continued in the hospital centers of the country, mainly at the General Hospital Babahoyo IESS, thus contributing to the integral rehabilitation of patients using cognitive-behavioral therapies, Rational emotive therapy, motivational therapies that help the patient improve, and reduce symptoms from the beginning, preventing the patient from reaching serious consequences for not being treated properly